Legitimacy Status of Inheritance by Adopted Children - Syaafiyah Abdullah; Aghny Nabila Fachruzia; Azhar Khoerul Bariyah Darda; Harmono Harmono; Moh. Sigit Gunawan (Return : Study of Management, Economic and Bussines, 2024)
This study aims to analyze the legal strength of civil registration deeds as evidence of inheritance ownership. The first research, How is the legal force of civil registration deeds as the basis for controlling inheritance by children. As an official document that records a person's birth, a birth certificate plays an important role in legal proceedings related to property inheritance. In the context of inheritance law, the validity of the birth certificate is the main key in determining the right of an adopted child to inherit property from his adoptive parents. Along with a valid birth certificate, the adopted child has a strong legal basis to claim his inheritance rights. However, there are challenges and problems that may arise related to the validity of birth certificates in the context of inheritance control. Second, how can heirs report criminal acts against adopted children who have controlled the inheritance. Therefore, this study aims to analyze in depth the role of birth certificate power as a tool that allows adopted children to obtain inheritance rights, as well as to identify strategies that can be applied to ensure the effective protection of inheritance rights of adopted children. Through the approach of legal analysis and literature study, this study concludes that the strength of the birth certificate is a crucial foundation in proving the legal status of an adopted child in the process of controlling inheritance, but further efforts are needed to improve the legal protection of adopted children in the context of property inheritance.